2017
DOI: 10.3892/ol.2017.6151
|View full text |Cite
|
Sign up to set email alerts
|

Acute myeloid leukemia with t(3;21)(q26.2;q22) developing following low-dose methotrexate therapy for rheumatoid arthritis and expressing two AML1/MDS1/EVI1 fusion proteins: A case report

Abstract: The t(3;21)(q26.2;q22) translocation is a rare chromosomal abnormality exhibited almost exclusively in therapy-related myelodysplastic syndrome/acute myeloid leukemia (t-MDS/AML) or in the blastic crisis phase of chronic myelogenous leukemia, which results in the fusion of the runt related transcription factor 1 (RUNX1, also called AML1) gene at 21q22 to the myelodysplasia syndrome 1 (MDS1)-ecotropic virus integration site 1 (EVI1) complex locus (MECOM) at 3q26.2, generating various fusion transcripts, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…High MECOM mRNA expression was observed in 10% of de novo AML, associated with a poor prognosis [2] . The MECOM gene can be rearranged with a variety of partner genes, such as ETV6 , RUNX1 , and so on [3,4] Organization (WHO) classification of myeloid neoplasms and acute leukemia recognized "AML with inv(3)(q21.3q26.2) or t(3;3)(q21.3;q26.2); GATA2 , MECOM " as a distinct entity [5] . Herein, we identified H2AFY as a novel fusion gene partner of MECOM in a patient with AML.…”
Section: Introductionmentioning
confidence: 99%
“…High MECOM mRNA expression was observed in 10% of de novo AML, associated with a poor prognosis [2] . The MECOM gene can be rearranged with a variety of partner genes, such as ETV6 , RUNX1 , and so on [3,4] Organization (WHO) classification of myeloid neoplasms and acute leukemia recognized "AML with inv(3)(q21.3q26.2) or t(3;3)(q21.3;q26.2); GATA2 , MECOM " as a distinct entity [5] . Herein, we identified H2AFY as a novel fusion gene partner of MECOM in a patient with AML.…”
Section: Introductionmentioning
confidence: 99%
“…The secondary abnormality t(3;21)(q26.2;q22) which developed following therapy in our patient is a rare abnormality and occurs in < 1% of cases with AML/MDS, primarily t-MDS/AML or in the blast phase of CML. It has been reported that these abnormalities occur particularly after chemotherapy and are associated with a poor prognosis [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, methotrexate use can increase the risk of secondary therapy‐related AML, and patients treated with methotrexate should be monitored for the development of AML. Noteworthy, the development of therapy‐related myelodysplastic syndrome/AML with t(8;21) and t(3;21) translocations was described in patients following low‐dose treatment with methotrexate for rheumatoid arthritis [ 6 ].…”
Section: Figurementioning
confidence: 99%